Civil engineering a very short introduction - Muir Wood, David 1949- (Oxford, United Kingdom Oxford University Press, 2012)
Civil engineering produces the structures of all human settlements worldwide and is a vital discipline for many aspects modern life, underlying housing, transport, and our major areas and buildings related to work, study, and leisure. In this Very Short Introduction, David Muir Wood demonstrates the nature and importance of civil engineering not only in the history of civilization and urbanization, but its range of facets today, and its challenges for the future. Beginning with the challenge of creating a settlement on a deserted island, which sets out the problems that civil engineers need to solve, he looks at the social and environmental considerations as well as the science, technology, and craft of building bridges, tunnels, houses, and areas of recreation. He highlights the lives of some major civil engineers, including Brunel and Bazalgette, considers the challenges of managing water and energy, and looks at our increasing sensitivity to building and the environment.
1. Materials of civil engineering -- 2. Water and waste -- 3. 'Directing the great sources of power in nature' -- 4. Concept, technology, realization -- 5. Robustness -- 6. Civil engineering: looking forward.
Includes bibliographical references (pages 131-135) and index.
Keywords: Civil engineering